Bibliometric study for CO2 measurement using IoT: Looking for the Latin American contributions - Páez-Carabajo, Juan Daniel (2022)
In recent years, the number of deaths due to environmental pollution has increased. The main air pollutants are carbon monoxide, carbon dioxide, and sulfur dioxide. These are produced by the consumption of fossil fuels in vehicles, industrial activity, and agricultural practices, among others. Various technologies have been used to detect carbon dioxide (CO2), including the Internet of Things (IoT). However, no studies have been carried out to visualize the impact of IoT on CO2 monitoring and which countries are focused on minimizing emissions. This work shows a bibliometric study for CO2 environmental sensing using IoT. SCOPUS was the selected database, and PRISMA was the methodology used. The first search returned 13.207 documents written between 2013 and 2022, after filtering selected keywords, selecting only English articles, and abstract review we selected finally 79 documents for the measurement of CO2 using IoT. The results of analyzing them, show that the Asian countries produces more than the western countries, where India and Indonesia are leading. Also is interesting to note that the USA and Latin America produced the same quantity of documents, where the four countries contributing to Latin America are Brazil, Mexico, Peru, and Ecuador. The main area of knowledge covered by the documents was Engineering with 25 percent followed by computer sciences, and 40 percent of documents were published by IEEE. Finally, the Latin American contributions to this field are outlined, verifying in detail the architectures for the proposed solutions with emphasis in sensors.